Reference and tutoring librarian in online distance education - Nóbrega, Paula Pinheiro da (2021)
Introduction: With the emergence of the Covid-19 pandemic in 2020, the world had to change habits to contain the disease, and one of them was to fulfill social isolation. Several sectors had to use the Internet, and Education was one of them. In the city of Fortaleza, a public university, on an urgent basis, promoted workshops for teachers and student monitors, in order to plan their classes and produce their teaching materials. In these workshops, the presence of a reference librarian contributed to the online tutoring process. Methodology: Based on the experience of librarian practice in online Distance Education tutoring, a bibliographic and descriptive research with a qualitative nature was adopted, serving as a basis for the experience report. Results: It was observed that the librarian, in online tutoring, has skills to develop functions, such as: guidance on sources of information, research, curatorship, among others. Conclusion: The reference librarian has skills and abilities in his training, whether to act in person or virtually, and, therefore, is able to carry out informational tutoring in online distance education.